Developments in Electrochemistry - Chun, Jang H. (IntechOpen, 2012)
The book "Developments in Electrochemistry" contains five feature articles in recent advanced electrochemistry. These selected feature articles emphasize physical phenomena rather than mathematical formalisms of electrochemistry. The topics represented in the book are: The phase-shift method and correlation constants for determining the electrochemical Frumkin, Langmuir, and Temkin adsorption isotherms at interfaces; Quantitative separation of an adsorption effect in the form of defined current probabilistic responses for catalyzed/inhibited electrode processes; A quick, simple, and non-invasive method to evaluate sudomotor dysfunctions; Cyclohexane-based liquid-biphasic systems for organic electrochemistry; Electrochemical transformation of white phosphorus as a way to compounds with phosphorus-hydrogen and phosphorus-carbon bonds. The work represented in this book will be useful, effective, and beneficial to physicists, chemists, surface scientists, material scientists, engineers, and especially electrochemists.